Egology and Hermeneutics: the Inspiration of Greimas and Kavolis in the Cultural Philosophy of Sverdiolas - Mažeikis, Gintautas (Problemos, 2020)
The purpose of the article is to analyze how existential phenomenology and hermeneutics of Sverdiolas helps to understand the formation of culture as a transcendental process in the periods of the social and cultural crisis. Sverdiolas explains in detail the egology of Greimas and the cultural sociology of Kavolis, their understanding of the crisis, the exile and decline of cultures, and the radical choices of public intellectuals. Since much is said about egology and participatory understanding, the article develops the concept of hermeneutical anthropology. In this connection, we discuss Sverdiolas’s relation to the hermeneutical anthropology of Cl. Geertz and the condition of the transgressive being, which partly explains the role of personal choice in the time of cultural crisis. The article asks where and how do existential hermeneutics become anthropological or sociological. Greimas is discussed in the context of the crisis of meaning and phenomenological egology, and Kavolis in the context of group symbolic interactionism, the sociology of trust and friendship.
Keywords: egology; transcendental ego; symbolic organization; existentialism; hermeneutics; phenomenology